Sites for wind-power installations: physical modeling of the influence of hills, ridges and complex terrain on wind speed and turbulence - Meroney, Robert N., author; Sandborn, Virgil A., author; Bouwmeester, R. J. B., author; Chien, H. C., author; Rider, M., author; Fluid Mechanics and Wind Engineering Program, Civil Engineering Department, Colorado State University, publisher (Colorado State University. Libraries, 1978)
Wind-tunnel model measurements have been performed to study the influence of topography profile, surface roughness and stratification on the suitability of various combinations of these variables for wind-power sites. For the range of examined cases (large turbulence integral scales with respect to surface feature scales) the flow is dominated by inviscid dynamics. Hence, the influence of hill shape, surface roughness, and mild stratification can be reliably estimated by simple prediction procedures for the range of situations considered (i.e., horizontal length scales of the order of 1000 meters). Detailed tables of velocity, turbulence intensity, pressure, spectra, etc., have been prepared to guide numerical model design and experimental rule of thumb constrictions. Cases include hill slopes from 1:2 to 1:20, neutral and stratified flows, two- and three-dimensional symmetric ridges, six alternate hill and escarpment shapes, and a variety of windward versus leeward slope combinations to evaluate ridge separation characteristics. In addition, one comparison program over complex terrain consisting of both field and laboratory measurements has been completed. The final product of this investigation is a summary of criteria to be satisfied for potential sites. Included was validation that certain criteria are satisfied which ensure similitude between the laboratory experiment and the atmospheric situation being modeled. The laboratory data were verified by comparison with field measurements in a well documented case of flow over known terrain. Emphasis was placed on effects of surface layer separation and topography scales larger than turbulence integral scales, i.e., hills small with respect to atmospheric surface layer depth.
Sites for wind-power installations: wind characteristics over ridges
Sites for wind-power installations: executive summary
Part I. Wind characteristics over ridges -- Part II. Final report: Executive summary -- Part II. Final report: Appendix.
CER77-78RNM-VAS50a-b.
CER77-78RJBB-RNM-VAS51.
For the United States Department of Energy, Division of distributed Solar Technology, Federal Wind Energy Program.
Keywords: Wind power